Complexity of mentalization - Arabadzhiev, Zlatoslav; Paunova, Rositsa (Frontiers in Psychology, 2024)
The ability to understand other people’s emotions, thoughts, and behaviors is associated with an individual’s ability and his attitude in the context of relationships. The development of this process is associated with different psychosocial factors: parental competence, building a secure attachment and reduced risk of violence in the family as well as the future intrapersonal relationships and social reality of one person Mentalization is empirically associated with resolving psychological tasks in normative dilemmas and also, can influence on the outcome of personal and situational crises. And so forth, passing through the different stages of life and prevention of dysfunctional patterns in the family is facilitated. This text aims to investigate the main characteristics of mentalization, its connection with the etiopathogenesis of some main mental disorders, their course and prognosis. Several studies in recent years confirmed that these connections can enroll mentalization to prevention and psychological therapy in some mental disorders and dysfunctional thinking patterns. On the other hand, it serves as a basis for psychotherapeutic competence expressed in the ability to connect, differentiate, and separate, as the main interactional stages of the psychotherapeutic process.